ANALISIS POTENSI DAN STRATEGI PENGEMBANGAN OBYEK WISATA ALAM AIR TERJUN TEROH TEROH DESA RUMAH GALUH KECAMATAN SEI BINGAI, KABUPATEN LANGKAT SUMATERA UTARA - Uli Irawati Panjaitan; Agus Purwoko; Kansih Sri Hartini (Program studi Kehutanan USU, 2016)
Indonesia is one of archipelago with famous natural resources either in land or in the sea. One of advantages is development of natural resources potency especially the forest resources. This research aims : (1) to analyze the potency of waterfall tourism object of Teroh Teroh in Desa Rumah Galuh, sub district of Sei Bingai, regency of Langkat, North Sumatera, (2) to analyze the development strategy of tourism object of waterfall of TerohTeroh in Desa Rumah Galuh, sub district of Sei Bingai, regency of Langkat, North Sumatera. The sample was took by purposive sampling method for the respondent who visit the object and random sampling for the society. The development strategy is formulated by identification of strength, weakness, opportunity and treat in the location of natural tourism object and analyzed by using SWOT Matrix. The results of research indicates that the natural tourism object of waterfall of Teroh Teroh in Desa Rumah Galuh, sub district of Sei Bingai, regency of Langkat, has natural tourism potency will be developed with the feasibility rate is 67.15 and on the first quadrant in SWOT Analysis. It means that the natural tourism of waterfall of teroh-teroh is in profitable condition with any strength either internal or external. Keywords : Wildlife Tourism, potency and development, Teroh Teroh waterfall, Rumah Galuh Vilage.